Pelepasan Informasi Medis Kepada Pihak Ketiga Di Rumah Sakit (Literature Review) - Anastasyannisa Ramadhanty; Nanda Aula Rumana; Deasy Rosmala Dewi; Noor Yulia (Yayasan Literasi Sains Indonesia, 2022)
Medical record information is confidential which must be protected from leakage of data/information in accordance with the medical code of ethics and applicable laws and regulations. The release of medical information must follow the applicable procedures, this aims to protect the hospital from further demands. This study aims to describe the suitability of SOPs for releasing medical information to third parties, types of requests for release of medical information and constraints in releasing medical information using fishbone diagrams. This research is a literature review study using a sample of 11 journals. Search articles using the Google Scholar database. The results of the study found that the percentage of compliance with SOPs for releasing medical information to third parties in hospitals was the percentage of releases that were in accordance with SOPs between 66%-82%, while the precentage that did not match the SOPs was between 18%-34%. The types of requests for release of medical information are for the purposes of visum et repertum, insurance and education. Constraints in releasing medical information to third parties in hospitals using fishbone diagrams are mostly found in Man, especially in patients/patient families do not bring complete requirements.